The Perception of Distance in Simulated Visual Displays:A Comparison of the Effectiveness and Accuracy of Multiple Depth Cues Across Viewing Distances - Surdick, R. Troy; Davis, Elizabeth T.; King, Robert A.; Hodges, Larry F. (Presence : teleoperators and virtual environment, 1997)
The ability effectively and accurately to simulate distance in virtual and augmented reality systems is a challenge currently facing R&D. To examine this issue, we separately tested each of seven visual depth cues (relative brightness, relative size, relative height, linear perspective, foreshortening, texture gradient, and stereopsis) as well as the condition in which all seven of these cues were present and simultaneously providing distance information in a simulated display. The viewing distances were 1 and 2 m. In developing simulated displays to convey distance and depth there are three questions that arise. First, which cues provide effective depth information (so that only a small change in the depth cue results in a perceived change in depth)? Second, which cues provide accurate depth information (so that the perceived distance of two equidistant objects perceptually matches)? Finally, how does the effectiveness and accuracy of these depth cues change as a function of the viewing distance? Ten college-aged subjects were tested with each depth-cue condition at both viewing distances. They were tested using a method of constant stimuli procedure and a modified Wheat-stone stereoscopic display. The perspective cues (linear perspective, foreshortening, and texture gradient) were found to be more effective than other depth cues, while effectiveness of relative brightness was vastly inferior. Moreover, relative brightness, relative height, and relative size all significantly decreased in effectiveness with an increase in viewing distance. The depth cues did not differ in terms of accuracy at either viewing distance. Finally, some subjects experienced difficulty in rapidly perceiving distance information provided by stereopsis, but no subjects had difficulty in effectively and accurately perceiving distance with the perspective information used in our experiment. A second experiment demonstrated that a previously stereo-anomalous subject could be trained to perceive stereoscopic depth in a binocular display. We conclude that the use of perspective cues in simulated displays may be more important than the other depth cues tested because these cues are the most effective and accurate cues at both viewing distances, can be easily perceived by all subjects, and can be readily incorporated into simpler, less complex displays (e.g., biocular HMDs) or more complex ones (e.g., binocular or see-through HMDs).